2004
DOI: 10.1364/opex.12.005625
|View full text |Cite
|
Sign up to set email alerts
|

Self-imaging phenomena in multi-mode photonic crystal line-defect waveguides: application to wavelength de-multiplexing

Abstract: We show that the self-imaging principle still holds true in multimode photonic crystal (PhC) line-defect waveguides just as it does in conventional multi-mode waveguides. To observe the images reproduced by this self-imaging phenomenon, the finite-difference time-domain computation is performed on a multi-mode PhC line-defect waveguide that supports five guided modes. From the computed result, the reproduced images are identified and their positions along the propagation axis are theoretically described by sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…1(b)]. According to the self-imaging principle in PCs [18,19], if the normalized frequency is chosen to be about a/λ = 0.425 (λ is the wavelength in free space), the minimal length of the multimode structure to achieve beam splitting is approximately 3π…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(b)]. According to the self-imaging principle in PCs [18,19], if the normalized frequency is chosen to be about a/λ = 0.425 (λ is the wavelength in free space), the minimal length of the multimode structure to achieve beam splitting is approximately 3π…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…For the beam-splitting function, it can also be achieved by means of multimode PCs [18]. As we know, the self-imaging principle still holds true in multimode PCs just as it does in conventional multimode waveguides [19]. And multimode PCs have been successfully applied in designing optical switches, power splitters, optical demultiplexers [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional WDM components are realized using arrayed waveguide gratings, thin-film filters and fibre Bragg gratings. Utilizing the extraordinary properties of PhCs many ideas including directional couplers, optical microcavities, multimode self-imaging waveguides, super-prisms and optical logic gates have been proposed [5][6][7][8][9][10]. In the near future, all these will be important components of logical processors for telecommunication networks and proper alternatives for electronic logic gates [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported that the self-imaging phenomenon is still available in a multimode PhC waveguide [13] as in a conventional multimode waveguide. A device based on the MMI effect in PhC can be much smaller than a conventional MMI device due to the large dispersion of a PhC structure.…”
Section: Introductionmentioning
confidence: 99%